Temporal Dynamics of the Interaction between Reward and Time Delay during Intertemporal Choice - Gui, Dan-Yang; Li, Jin-Zhen; Li, Xiaoli; Luo, Yue-jia (Frontiers in Psychology, 2016)
Intertemporal choice involves the processes of valuation and choice. Choice is often the result of subjective valuation, in which reward is integrated with time delay. Here, using event-related potential (ERP) signals as temporal hallmarks, we aim to investigate temporal dynamics of how reward interacts with time delay during a delayed discounting task. We found that participants preferred immediate rewards when delayed rewards were small or over long-term delays. Our ERP results suggested that the P200 component reflected an initial valuation of reward and time delay, while the frontal N2 component correlated with individual choices of immediate option of rewards. The LPP component was modulated by the N2 component. These findings demonstrate that the N2 component is the key component in temporal dynamics of the interaction between reward and time valuation.